2015
DOI: 10.1007/978-3-662-48561-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Learning Actions Models: Qualitative Approach

Abstract: In dynamic epistemic logic, actions are described using action models. In this paper we introduce a framework for studying learnability of action models from observations. We present first results concerning propositional action models. First we check two basic learnability criteria: finite identifiability (conclusively inferring the appropriate action model in finite time) and identifiability in the limit (inconclusive convergence to the right action model). We show that deterministic actions are finitely ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…1 The emergence of the stronger epistemic state of irrevocable knowledge can be linked to a more restrictive kind of identifiability, finite identifiability [see 19,20,27]. It has also been recently investigated in the context of action learning in dynamic epistemic logic [16,17]. 2 Note that we interpret s t as 's is at least as plausible as t'.…”
mentioning
confidence: 99%
“…1 The emergence of the stronger epistemic state of irrevocable knowledge can be linked to a more restrictive kind of identifiability, finite identifiability [see 19,20,27]. It has also been recently investigated in the context of action learning in dynamic epistemic logic [16,17]. 2 Note that we interpret s t as 's is at least as plausible as t'.…”
mentioning
confidence: 99%
“…The algorithms use dynamic epistemic logic (DEL) to represent the learned domain information symbolically. Our work continues that of Bolander and Gierasimczuk (2015), which developed DEL-based learning algorithms based to learn domain information in fully observable domains.…”
mentioning
confidence: 66%
“…This work builds upon the framework by Bolander and Gierasimczuk [13,14], where two basic learnability criteria for actions were studied: finite identifiability (conclusively inferring a representation of the correct action in finite time) and identifiability in the limit (inconclusive convergence to a representation of the right action). It has been shown that deterministic actions are finitely identifiable, while arbitrary (nondeterministic) actions are only identifiable in the limit, in the fully observable setting.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, in addition to approaches such as [22,75], there have been a number of advances recently on learning dynamic representations (e.g., [68]), which might provide fertile ground to lift such ideas for cognitive robotics. Computability results for qualitative learning in dynamic epistemic logic has been studied in [16]. Recently, proper + knowledge bases were shown to be polynomial-time learnable for querying tasks [5].…”
Section: Related Work and Discussionmentioning
confidence: 99%